Steuerliche Gewinnverteilung bei Personengesellschaften Eine vergleichende Analyse der Rechtsordnungen Deutschlands, der USA und des Vereinigten Königreichs - Abel, Juliane (Steuerwissenschaftliche Schriften, 2022)
The German Income Tax Act simply states that partners must pay tax on their share of the partnerhip's profits. The amount of this share is based on the profit distribution agreement under private law, which the partners are largely free to structure. In contrast, the U.S. tax code provides detailed rules for the distribution of partnership taxable income, and the United Kingdom has also recently considered a reform of the law. Against this background, the dissertation evaluates the fundamentals of the allocation of partnership profits and losses under German tax law in the light of a detailed legal comparison with US and UK law. Based on this, important practical cases are discussed and a legislative proposal for a new regulation is presented.